Career self-efficacy as a mediator between school counseling and career indecision: a systematic literature review - Yetti Helda; Miftahul Fikri; Yeni Karneli; Rezki Hariko (Journal of Counseling, Education and Society, 2026)
Career indecision remains a major challenge in school-to-work transitions among vocational education students, whose career exploration is often constrained by early exposure to workplace demands and vocational curricula. This study systematically reviewed the relationship between career self-efficacy and career indecision and examined the role of school career counseling among vocational education students. Following the PRISMA 2020 framework, a systematic search was conducted in the Scopus database using terms related to career self-efficacy, career indecision, career decision-making, vocational education, and school/career counseling. Study quality was assessed using the four-domain FICO framework, and findings were synthesized thematically. The search identified 191 records, of which 50 articles from various countries and contexts were included, primarily published between 2011 and 2023. Four themes emerged: career decision-making self-efficacy consistently predicted lower career indecision and greater career adaptability; social support from parents, teachers, and counselors strengthened self-efficacy; structured career guidance reduced irrational career beliefs and indecision, although evidence among vocational high school students remained limited; and psychological assets such as resilience, proactive personality, and emotional intelligence influenced the self-efficacy–indecision relationship. The findings support Social Cognitive Career Theory and suggest that vocational schools should incorporate structured, counselor-led self-efficacy development activities. Further research is needed across diverse vocational education contexts, particularly beyond East Asian settings.